Prospecting for geothermal energy through satellite based thermal data: Review and the way forward - F. Howari (Global Journal of Environmental Science and Management)
Geothermal investors need to be confident with the methods and results of exploration programs. Also cutting the upfront cost of geothermal exploration will further encourage investors to consider investment in this emerging clean energy field. Hence, it is of paramount importance to improve prospecting techniques in order to explore where economic concentrations of geothermal energy are to be expected.  The current study evaluates different approaches for downscaling thermal data from remote sensing images together with factors in surface and subsurface environment. The paper discusses case studies, the challenge and the way forward for geothermal prospecting as well as practical solutions to discrepancy that faces the mapping and documentation of spatial geothermal anomalies.  It also discusses main criteria that should be considered while prospecting for geothermal energy.